2013
DOI: 10.2147/opth.s38194
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in Cameroonians diagnosed with complete oculocutaneous albinism

Abstract: BackgroundAlbinism causes significant eye morbidity and amblyopia in children. The aim of this study was to determine the refractive state in patients with complete oculocutaneous albinism who were treated at the Gynaeco-Obstetric and Paediatric Hospital, Yaoundé, Cameroon and evaluate its effect on vision.MethodsWe carried out this retrospective study at the ophthalmology unit of our hospital. All oculocutaneous albino patients who were treated between March 1, 2003 and December 31, 2011 were included.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…As a result, they are caught in a vicious circle of the poor development and social ostracism. In the current study, that all the eyes had visual impairment with the majority (38%) of them having moderate VI can be explained in part by higher refractive error that was amblyogenic and in part by other factors, such as hypoplastic foveae, squint, nystagmus, and photophobia; this is consistent with the results by Eballé et al 12 who reported that the majority (70%) of the eyes had moderate visual impairment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, they are caught in a vicious circle of the poor development and social ostracism. In the current study, that all the eyes had visual impairment with the majority (38%) of them having moderate VI can be explained in part by higher refractive error that was amblyogenic and in part by other factors, such as hypoplastic foveae, squint, nystagmus, and photophobia; this is consistent with the results by Eballé et al 12 who reported that the majority (70%) of the eyes had moderate visual impairment.…”
Section: Discussionsupporting
confidence: 92%
“…2 Mvogo et al, in their study, reported the prevalence of 61.9% and Eballe et al observed that of 40% establishing myopic astigmatism to be the most common refractive error in albinos. 12 , 19 This study also found the similar result in which 34% of the cases had myopic astigmatism making it the most prevalent refractive error in patients with OCA. On the contrary, other studies reported hypermetropia to be the most common refractive error.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In another study of 50 eyes of 25 patients with oculocutaneous albinism, distance visual acuity was found to be 1.24 ± 0.50 log MAR 9 . Eballe AO et al reported moderate visual impairment (0.48 < VA ≤ 1.00 log MAR) in 70% of patients 11 . Twenty five patients of albinism were reported in another study with 7 ocular albinism and 18 oculocutaneous albinism, the mean visual acuity was 0.9 log MAR 12 .…”
Section: Discussionmentioning
confidence: 96%
“…Our observations in this study is similar to the results reported by Udeh., et al and Ajose., et al in other parts of Nigeria [11,13]. Other developing countries with similar socioeconomic status such as Nepal, Cameroun and Malawi also had similar findings [17][18][19]. It has been postulated that the subnormal presenting visual acuity may be due to delayed visual maturation, foveal hypoplasia, nystagmus, strabismus and iris trans-illumination.…”
Section: Discussionmentioning
confidence: 69%